Advances in bioinks and in vivo imaging of biomaterials for CNS applications - Oliveira, Maria Eduarda Moreira Pinheiro Santo (2019)
Due to increasing life expectancy incidence of neurological disorders is rapidly rising, thus adding urgencyto develop effective strategies for treatment. Stem cell-based therapies were considered highly promisingand while progress in this field is evident, outcomes of clinical trials are rather disappointing. Suboptimalengraftment, poor cell survival and uncontrolled differentiation may be the reasons behind dismal results.Clearly, new direction is needed and we postulate that with recent progress in biomaterials and bioprint-ing, regenerative approaches for neurological applications may be finally successful. The use of biomate-rials aids engraftment of stem cells, protects them from harmful microenvironment and importantly, itfacilitates the incorporation of cell-supporting molecules. The biomaterials used in bioprinting (thebioinks) form a scaffold for embedding the cells/biomolecules of interest, but also could be exploited asa source of endogenous contrast or supplemented with contrast agents for imaging. Additionally, bioprint-ing enables patient-specific customization with shape/size tailored for actual needs. In stroke or traumaticbrain injury for example lesions are localized and focal, and usually progress with significant loss of tissuevolume creating space that could be filled with artificial tissue using bioprinting modalities. The value ofimaging for bioprinting technology is advantageous on many levels including design of custom shapesscaffolds based on anatomical 3D scans, assessment of performance and integration after scaffold implan-tation, or to learn about the degradation over time. In this review, we focus on bioprinting technologydescribing different printing techniques and properties of biomaterials in the context of requirementsfor neurological applications. We also discuss the need forin vivoimaging of implanted materials and tis-sue constructs reviewing applicable imaging modalities and type of information they can provide.